Role of Endoscopic Skull Base and Keyhole Surgery for Pituitary and Parasellar Tumors Impacting Vision. Issue 4 (December 2015) - Kelly, Daniel F.; Griffiths, Chester F.; Takasumi, Yuki; Rhee, John; Barkhoudarian, Garni; Krauss, Howard R.
Abstract : Abstract: Significant advances over the last 2 decades in imaging technology, instrumentation, anatomical knowledge, and reconstructive techniques have resulted in the endonasal endoscopic approach becoming an integral part of modern skull base surgery. With growing use and greater experience, surgical outcomes continue to incrementally improve across many skull base pathologies, including those tumors that impact vision and ocular motility. The importance of the learning curve and use of a multi-disciplinary approach is critical to maximizing success, minimizing complications, and enhancing quality of life in these patients. Realizing the limits of the endonasal route and reasonable use of transcranial approaches such as the supraorbital eyebrow craniotomy is also critical, as is appropriate use of nonsurgical therapies including various forms of radiotherapy, radiotherapy, and medical treatment options. Abstract : Supplemental Digital Content is Available in the Text.